Utilization of low-cost substrates for the production of high biomass, lipid and docosahexaenoic acid (DHA) using local native strain Aurantiochytrium sp. YB-05 - Mohamed A. Abdel-Wahab; Abd El-Rahim M.A. El-Samawaty; Abdallah M. Elgorban; Ali H. Bahkali (Journal of King Saud University: Science, 2022)
This study explores low-cost substrates for the production of high biomass, lipid and DHA by local native strain of thraustochytrid that was isolated from decaying leaves of Avicennia marina collected from Yanbu mangroves along the Red Sea coast of Saudi Arabia. Molecular phylogenetic analyses based on 18S rDNA sequences placed the thraustochytrid strain (YB-05) in the Aurantiochytrium. The studied strain was grown on three different types of raw material available in the local market and compared to pure glucose for high biomass, lipid and DHA production. Aurantiochytrium sp. YB-05 was grown on: date fruit, glycerol, cane molasses and pure glucose at four concentrations: 10, 20, 40 and 80 g/L. Produced dry cell weight increased as the carbon sources: date fruit, molasses and glucose increased from 10 to 80 g/L. Both date fruit and molasses gave a higher biomass than pure glucose and glycerol at 40 and 80 g/L concentration, while glucose gave higher biomass at 10 and 20 g/L than the other three carbon sources. Date fruit gave the highest biomass (42.6 g/L) at the 80 g/L concentration and also increased the level of DPA (decosapentaneoic acid) and DHA from 0.64 and 4.89% TFA (total fatty acids) with glucose to 7.13 and 24.85% with date fruit respectively. Ten g/L glycerol gave the highest percentage of lipids (85.6% of the biomass), followed by 40 g/L glucose (80.1%), 20 g/L glycerol (70%), 80 g/L glucose (59.3%) and 80 g/L date fruit (56.4%). The percentage of lipid in the biomass increased with increasing the weight of date fruit and molasses from 10 g/L (24.7% and 15.6% respectively) to 80 g/L (56.4% and 45.7% respectively). This study shed a light on the potential use of date fruits for the production of value-added products using microbes. Saudi Arabia is the second largest date producer in the world after Egypt. The present research also studied the effect of four types of oily seeds in a combination with date fruit on the production oil, DHA and the major fatty acids produced by Aurantiochytrium sp. YB-05. The fatty acid profile of Aurantiochytrium sp. YB-05 grown on date palm, pure glucose and seeds were determined.